METODE EKSTRAKSI DNA CABAI (Capsicum annuum L.) MENGGUNAKAN MODIFIKASI BUFFER CTAB (CETHYL TRIMETHYL AMMONIUM BROMIDE) TANPA NITROGEN CAIR - Kristianto Nugroho; Rerenstradika T Terryana; Puji Lestari (Scripta Biologica, 2017)
Chili pepper is an agricultural commodity having high economic value. The production and supply of chili pepper frequently did not match the increased demand; it caused the market price fluctuated. It is important to create new varieties of chili pepper with high production trait to overcome the scarcity. Therefore the plant breeding activities for chili pepper should be done intensively in both conventional and molecular-based to obtain varieties of chili pepper with expected qualities. In molecular breeding, DNA extraction is the crucial steps of the process. If extracted DNA has an excellent quality and quantity,  the next processes normally could be completed with the high-quality result. To date, most methods of DNA extraction used liquid nitrogen to destroy the tough carbohydrates of plant tissue. Liquid nitrogen is nitrogen gas in a fluid state which quite difficult to be distributed to the remote laboratory wit no available storage facility. This study aimed to obtain a modified DNA extraction method, in particular for chili pepper, which capable to produce DNA with high quality and quantity without using liquid nitrogen. The sample used consisted of eight F2 plants including their hybrid-parental of the Kencana and the 0207. This research applied modified Doyle and Doyle method for extraction. Modification of extraction buffer is done through the addition of the 1% (w/v) PVP (Polyvinylpyrrolidone) and 0.2% (v/v) β-mercaptoethanol. The results showed that the DNA extracted using this method has good quality and quantity, capable of being amplified by using SSR (Simple Sequence Repeat) primer and could be digested by restriction enzyme EcoRI. Besides, this method can reduce dependence on the use of liquid nitrogen, in particular for remote laboratories with no available storage facility.